Measuring the system size dependence of the strangeness production with ALICE - Nepeivoda Roman (EPJ Web of Conferences)
The system size dependence of strangeness production in highenergy collisions was studied using Run 2 data from the ALICE experiment at the LHC. The analysis examines the ratios of strange hadron yields to pion yields as a function of mid-rapidity charged particle multiplicity ⟨dNch/dη)|η|&0.5, offering insights into the mechanisms driving strangeness enhancement across different collision systems (pp, p–Pb and Pb–Pb). The yield ratios exhibit a continuous rising trend from low-multiplicity pp collisions at √s = 7 TeV to central Pb–Pb collisions at √sNN = 5.02 TeV. Additionally, the evolution of the mean transverse momentum (⟨pT⟩) for various strange hadrons (KS0, Λ(Λ¯), Ω±, Ξ±) is analyzed, revealing that ⟨pT⟩ does not connect smoothly between different collision systems, with harder spectra observed in high-multiplicity pp collisions compared to the peripheral Pb–Pb collisions. Finally, performa plots from LHC Run 3 are presented, showcasing the purity of Ξ− and Ω− invariant mass distributions and highlighting the enhanced detector capabilities in Run 3.